Solubility of isoniazid in supercritical carbon dioxide - Heryanto, Rudi; Abdullah, Ezzat Chan; Hasan, Masitah (American Chemical Society, 2010)
Solubility data of isoniazid in supercritical carbon dioxide are important in selecting the most appropriate supercritical methods for pharmaceutical material processing, such as the micronization of isoniazid or the production of isoniazid composites. The solubility of isoniazid in supercritical carbon dioxide was measured using a dynamic analytical method at temperatures of (308, 311, and 313) K and pressures ranging from (13.0 to 18.5) MPa. The result showed that isoniazid solubility increased with the increase of pressure at an isothermal condition and it also increased with the increase of temperature. The experimental data were correlated using the Chrastil and Mendez-Santiago and Teja models. The calculated results show good agreement with the experimental data.